Character Formation of Nutrition Aware Adolescents in an Effort to Prevent Triple Burden in Students of the Civil Integrated Model High School in Palu City - Putu Candriasih; Sri Restu Tempali; Wijianto Wijianto; Taslim Taslim (Poltekkes Kemenkes Palu, 2023)
Teenagers are one of the determinants of quality and highly competitive human resources (HR). Improving nutrition is not only focused on the first 1000 HPK but also during adolescence. From RISKESDAS data (2018), adolescents aged 13-18 years have a short and very short nutritional status of 51.6%. thin and very thin 16.8%, overweight and obese 29.5%. And 32% aged 15-24 years are anemic. There are three burdens of nutritional problems (triple burden), namely stunting, wasting, obesity and micronutrient deficiencies, namely anemia. Another problem is that 65% of teenagers do not eat breakfast, 97% do not consume enough vegetables and fruit, lack physical activity and. For this problem, it is necessary to build the character of nutritionally aware teenagers through the implementation of local balanced nutrition. The aim is to see changes in adolescent behavior regarding local balanced nutrition. Research method Type of experimental research, with a quasi-experimental approach to pre-post-test one group design using the Accidental Sampling technique, a sample of 63 students at Madani High School, Palu City. The research results showed that the majority of respondents had good knowledge, but there were still some who did not know enough about balanced nutrition. Most attitudes show good positive results and good positive behavior assessment results. Knowledge is good, but implementation is still lacking, so it is necessary to build character in teenagers by implementing balanced nutrition through regular plate contents.